Aerodynamic performance of cycling time trial helmets - Blair, K.; Sidelko, S. (The Engineering of sport 7, Volume 1, 2008)
The aerodynamic performance of equipment is critical for cycling's "race of truth", the time trial, where time differences of seconds can separate the top finishers. Recently several manufacturers have developed aerodynamic helmets specifically for use during time trials. To date, a comprehensive study of the aerodynamic performance of these time-trial helmets has not been performed. In this study, the aerodynamic helmets were tested on a mannequin in the time trial positions over a range of yaw angles, from 0° to 15°, in increments of 5°. The helmets were tested at three head angle positions at each yaw angle in order to best mimic actual riding conditions. A control road helmet was used to serve as a comparative tool. The testing results showed that all of the aerodynamic helmets offer drag reduction over a Standard road helmet. However, the ranking of helmets in order of performance varied depending on yaw angle and head angle.